Doxorubicin cardiotoxicity and target cells: a broader perspective. Issue 1 (December 2016) - De Angelis, Antonella; Urbanek, Konrad; Cappetta, Donato; Piegari, Elena; Ciuffreda, Loreta; Rivellino, Alessia; Russo, Rosa; Esposito, Grazia; Rossi, Francesco; Berrino, Liberato
Abstract The cardiotoxicity of doxorubicin is becoming an interdisciplinary point of interest given a growing population of cancer survivors. The complex and not completely understood pathogenesis of this complication makes difficult to design successful preventive or curative measures. Although cardiomyocyte has been considered a classical cellular target, other cells including various types of undifferentiated cells are involved in myocardial homeostasis. Such perspective may shed light on previously unrecognized aspects of cardiotoxicity and promote new experimental and clinical cardioprotective strategies. In this review, different cellular targets of doxorubicin are discussed with the focus on cardiac progenitor cells, oxidative stress, DNA damage, senescence and apoptosis all of which contribute to their compromised functional properties.